EVALUATION OF THE IMPLEMENTATION OF ISO 9001 QUALITY MANAGEMENT SYSTEM AND ITS INFLUENCE TO THE MANAGERIAL PERFORMANCE AND THE CONSISTENCY OF THE VACCINE PRODUCT QUALITY IN PT. BIO FARMA (PERSERO) - Rika Murhayanti; Marchaban Marchaban; Akhmad Kharis Nugroho (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
ISO 9001 is an international standard which commonly used for certification related to the quality management system of company or organization eventhough not all of organization that implemented ISO 9001 seems to get the benefit related to higher organizational performance or consistency of products quality. This research aims to evaluate the implementation of ISO 9001 in the quality management system of PT. Bio Farma (Persero), to find out the influence of the implementation of the ISO 9001 quality management system on the managerial performance and on the consistency of vaccine products quality in PT. Bio Farma (Persero). This research was descriptive analysis retrospective research. The data collected are from the observation on the implementation of ISO 9001, the interview with the related parties, and the document review. The documents reviewed are the manual system guide, Standard Operating Procedure, Report of the Key Indicator Performance, and Report of Annual Product Review (APR). The result of the research shows that PT. Bio Farma (Persero) has already implemented the required elements of the ISO 9001 quality management system were Quality management system (100%), 2) Management responsibility (99,2%), 3) Resources management (100%), 4) Product realization (99,2%), 5) Measurement, analysis and improvement (100%). The implementation of the ISO 9001 quality management system improves the managerial performance of the company, whereas the key performance indicator in the last four years was always achieved, even there was improvement in achievement minimum standard. The consistency of the vaccine quality in the last three years was always achieved as observed from DTP-HB vaccine’s quality parameter that shows the process was capable (Process Capability Index (Cpk) ≥ 1), except for pH parameter within the year of 2007 (Cpk = 0,55) and year of 2009 (Cpk = 0,92); and MWGT parameter within the year of 2007 (Cpk = 0,75). Keywords: quality management system, ISO 9001, managerial performance, consistency of products quality